Exploring Women’s Marginalization in Selected Poems from ’Dear Girl’ by Aija Mayrock - Vera Wanda Sari Ayu (Morphosis: Journal of Literature, 2024)
The aim of this study entitled “Women’s Marginalization in Selected Poems of Dear Girl by Aija Mayrock” was to analyze the issue of marginalization against women as depicted in selected poems from Aija Mayrock’s “Dear Girl” (2020). “Dear Girl” (2020) mostly showed poetries that speak about the injustice faced by women in society which make women experience marginalization. In addition, “Dear Girl” also consists of inspirational messages from the speaker and her empowerment of women so that they can occupy equality and equal rights like men. This study uses qualitative methods to analyze and reveal the phenomenon of marginalization in the form of gender-based unfair treatment that is carried out by society unconsciously in social life, especially to women. The data were analyzed through words and quotations by using Simone De Beauvoir’s (1953) feminism theory and presented in the form of an essay. The results of the study showed that marginalization depicted in the poems was influenced by the position of women who were considered inferior in society due to the social construction and social values that were not in their favor, the marginalization also occurs since women were considered unable to decide because of the society’s paradigm of their nature and also the patriarchal system that marginalize women so that they cannot make their own decisions, then the domestication also triggers marginalization because women cannot freely play their roles in public spaces. Keywords: decision making, feminism, marginalization, public space, qualitative methods